2023
DOI: 10.1590/fst.102322
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and antioxidant activity of polysaccharides copper from Qingzhuan dark tea

Abstract: Tea polysaccharides was one of the active ingredients of Qingzhuan dark tea, which had antioxidant, anti-tumor, and immuneenhancing effects. The complexation of metal ions of tea polysaccharides was one of the current research hotspots. It can combine the advantages of tea polysaccharides and their complexed trace metal elements, and had great potential development. In this study, the trace element-copper required by the human body was used for complexation with Qingzhuan dark tea polysaccharides, and the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The concentration of the non‐chelated Fe 2+ in the supernatant in Preparation of egg yolk peptides‐Fe (EYP‐Fe) complexes was measured according to Hou et al ., (2009). Briefly, two drops of phenanthroline were added to 4 mL supernatant and reacted for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of the non‐chelated Fe 2+ in the supernatant in Preparation of egg yolk peptides‐Fe (EYP‐Fe) complexes was measured according to Hou et al ., (2009). Briefly, two drops of phenanthroline were added to 4 mL supernatant and reacted for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…And the possible regulatory pathways of tea on glucolipid metabolism were as follows: inhibiting lipid absorption by forming complex with lipids and lipases (Xu et al, 2020), reducing glucose digestion and absorption by inhibiting amylase activity (Sun et al, 2017), inhibiting gluconeogenesis (Collins et al, 2007), enhancing glucose consumption and utilization (Lin & Lin, 2008) etc. Of course, researchers suggested that tea polyphenols (TPs) (Macena et al, 2022;Tan et al, 2022), caffeine (CAF), tea polysaccharide (Zhou et al, 2022a(Zhou et al, , 2023Kim et al, 2022), and other functional ingredients (Rubanka et al, 2020;Wang et al, 2023) contained in tea play a key role in lowering blood glucose levels. In addition, studies suggested that TPs (Zhou et al, 2022b), tea pigment (Liu et al, 2020) and other functional components contained in tea also play an important role in lowering uric acid levels.…”
Section: Introductionmentioning
confidence: 99%